Masks from many cultures (Glenview, Il. Crystal Productions, 1993)
Shows a variety or ancient and contemporary masks from all over the world and explains how they are used in rituals, festivals, and as artistic objects.
VHS format.
Director, Tom Hubbard ; writer, Lory Hubbard.
Includes images of over 100 masks with are combined with sequences of dances and festivals where masks are worn. Among the masks presented are examples from New Guinea, Bali, China, Tibet, Japan, Korea, Africa,Mexico, Guatemala, Bolivia, as well as a variety of masks by North American Indians.-Container.
Keywords: Masks in art; Masks; Masks -- Social aspects